Sustainable Consumption : Consumer Behavior When Purchasing Sustainability-Labeled Food Products - Sharief, Zainab; Panghal, Anupama (Indian Journal of Marketing, 2023)
Purpose : With growing concern about sustainability, consumers are trying to make sustainable purchase decisions. Sustainability labels are visual communicators of sustainability product information differentiating between conventional and sustainable products. Various studies reported positive consumer behavior toward sustainable consumption. This paper aimed to identify the factors influencing consumers’ behavior while purchasing sustainability-labeled food products and the moderating effect of the income variable. Methodology : For the study, five hypotheses were developed from relevant literature support to form a conceptual framework. Atotal of 498 Indian consumers participated in the survey. The variables selected for the study were validated by confirmatory factor analysis. The proposed model was examined using structural equation modeling. The correlation between constructs correlation was measured, and the overall model fit was validated. Confirmatory factor analysis was used to validate the variables selected for the study. Structural equation modeling was used to test the proposed model. Correlation among constructs was measured. Analysis of moment structure was used to assess the overall model fit. Findings : The study revealed that the five constructs, namely, purchase intention, awareness, environmental consciousness, moral obligations, and subjective norms, significantly influenced consumer behavior. Further, it was substantiated with a good model fit with consumer income as the moderating factor. The study supported the applicability of Ajzen’s theory of planned behavior. Practical Implications : The study’s findings will affect the food processing industry and third-party certification agencies. This study will guide policymakers by providing significant insights into consumer behavior toward sustainability-labeled food products. The study also provided suggestions to promote sustainability labels that are currently voluntary. Value : The proposed model in the study helped understand the Indian consumer behavior toward sustainability-labeled food products and promote sustainable consumption and production among various stakeholders of the food processing industry.